Pellets recovered from stick nests and new diet items of Furnariidae (Aves: Passeriformes) - Turienzo, Paola Noemí (2014)
This is the first record showing eleven species in seven genera of Furnariidae (Aves: Passeriformes) from Argentina that regurgitate pellets. A total of 627 nests of Furnariidae was examined, and from 84 nests (13.3%), 1,329 pellets were recovered. These pellets were found in the closed, domed nests of many Furnariidae, because in comparison to other passerine birds, their nests were used for roosting, especially in the subfamily Synallaxinae. Anumbius annumbi had the highest percentage of nests containing pellets. Food items identified from the pellets provided important new data on the diets of several species of Furnariidae.